ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP HAK CIPTA - Chairan, A. Tenripadang (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2011)
This paper describes the analyst Juridical Protection of copyright law. From the assessment results with normative legal approaches gained an understanding that the Copyright Act provide adequate legal protection for the creator or copyright holder, as well as protection measures include: 1) Copyright is the right of the imateriil material and attached to a personal creator and can be transferred, 2) legal protection for a specified period, 3) Imposition of sanctions against violators, and 4) for certain circumstances, copyright can be social. From an economic perspective, giving copyright protection to do because it contains economic potential.